Has Computerization Changed Translation? - Mossop, Brian (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2006)
AbstractBecause of the hype surrounding computers, it is hard to determine whether they are doing anything more than speed up the writing and research process. Changes such as the advent of ‘collage’ translations – where phrases are pasted into translations from old translations or original TL documents – have been enabled by technological change but they are driven by changes in the translation business.